A guide to planning and managing open innovative ecosystems - Leitão, João; Ratten, Vanessa; Barroca, Jean (Emerald Publishing, 2020)
Digital technology in the form of big data and data analytics is transforming the global economy. This book is the first to take an open innovation perspective to the study and practice of ecosystems, providing a novel way of understanding the impact data has on the way entrepreneurial firms develop. Governments are emphasising the use of open innovation ecosystems due to increased levels of digitalization in the global economy. This enables information and knowledge to be disseminated in a way that enables entrepreneurial projects to develop. Written primarily for practitioners and academic researchers, A Guide to Planning and Managing Open Innovative Ecosystems focuses on the unique nature of open innovation by utilising a government and data perspective. This helps to understand the dynamic manner in which digital technology in the form of big data is changing society. The role of the government in influencing an open innovation culture in society is discussed through the use of different cultural examples, enabling a holistic perspective about how government and data are influencing entrepreneurial endeavours
Includes index. - Includes bibliographical references. - Print version record
Keywords: Business enterprises; Computer networks; Software ecosystems; Entrepreneurship; Business & Economics; Entrepreneurship; bisacsh; Business mathematics & systems; bicssc